The problem of Lebenswelt in Maurice Merleau-Ponty’s late philosophy - Wesołowska, Agnieszka (Folia Philosophica, 2009)
In this paper I focus on the Merleau-Ponty’s conception of Lebenswelt. Derived from Husserl this conception appears to be the core problem of Merleau-Ponty’s late philosophy, especially in his The visible and the invisible. Here I focus on the problem of the correlation of Lebenswelt and existence. While dealing with the idea of Lebenswelt Merleau-Ponty works out the categories of his philosophy, such as the conception of body taken as chiasm or the potentiality of diversity, and the vertical perspective of being in the world. All these issues, as seen in The visible and invisible, are connected with the conception of Lebenswelt. In the paper the originality of Merleau-Ponty’s philosophy is pointed out. In his attempts for trying to consolidate the world in its inseparable unity with the existence, he reveals the source character of man’s relation with Lebenswelt that is with the world in which both body and speech take part.